Penerapan Media Digital Bookbot untuk Meningkatkan Kemampuan Membaca Permulaan pada Anak dengan Kesulitan Belajar : The Implementation of Bookbot Digital Media to Improve Early Reading Skills in Children with Learning Difficulties - Fitri Yuliastuti; Ibnu Syamsi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to improve early reading skills in students with learning difficulties by using the Bookbot digital tool in an inclusive primary school. Early reading is a fundamental skill that largely determines a student's success in subsequent stages of learning. However, students with learning difficulties often face obstacles in recognising letters, blending syllables, reading simple words, and comprehending basic texts. The study employed the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted over two cycles, each comprising planning, action implementation, observation, and reflection phases. The subjects were five first-grade students experiencing difficulties with early reading at an inclusive primary school. Data were collected through early reading assessments, observations of the teaching-learning process, and documentation, then analysed using both qualitative and quantitative descriptive methods based on learning mastery percentages. The results indicate that during the pre-cycle stage, none of the students met the Learning Objective Achievement Criteria (KKTP), resulting in a 0% mastery rate. Following the intervention in Cycle I, the mastery rate rose to 60% and subsequently increased to 80% in Cycle II, with four out of the five students successfully meeting the KKTP. This improvement was supported by the tool's presentation, which integrates visual, audio, and digital interactive elements, thereby enhancing student attention, motivation, and engagement during the learning process. Thus, the Bookbot digital tool is effective for improving early reading skills among first-grade students with learning difficulties in an inclusive primary school setting.